Implementasi Pendidikan Agama Islam Dalam Pembiasaan Nilai-Nilai Cinta Al-Qur'an Pada Peserta Didik - Ahmad Faiz; Romlah Widayati; Muh. Ubaidillah Al Ghifary S. (CV. Doki Course and Training, 2024)
Purpose- This study aims to explore how Islamic religious education is being implemented at MI Birrul Walidain Darussalam Tangerang through the values of the religion of love Al-Qur’an Learning Tahsin and Tahfidz, reveal the implications of using this strategy and reveal development plans for the future. Methods- This study uses qualitative methods to conduct field research. Primary and secondary data are two different categories of data. Techniques for collecting data include observation, interviews, and documentation. Findings - The results of this study indicate that 1). The implementation of learning to Love the Qur’an through Tahsin and Tahfidz at MI Birrul Walidain Batuceper has 3 aspects, namely in terms of planning, implementation and evaluation, 2). The implementation of the use of learning the Love of the Qur’an, namely Tahsin and Tahfidz at MI Birrul Walidain Batuceper is that the teacher can deepen the knowledge of the Qur’an and repeat the memorization that has been owned, reduces student difficulties, students have better morals, understand more content of verses, more disciplined, hardworking, patient, independent, honest, grades can be on target, achievers, have a good impact on the environment, a school atmosphere that loves the Qur’an, parents of students participate in Tahsin learning, and alumni become donors, and 3 ). The plan for developing the Tahsin and Tahfidz Al-Qur’an learning strategy at MI Birrul Walidain Batuceper for the future is to make a special Tahsin and Tahfidz program, hold seminars, memorize the Al-Qur’an community, train teachers, make it a special class, make certificates, graduation, acceleration, allocating funds, freeing tuition fees, facilitating students to enter universities, requirements for taking diplomas, and cooperation with Tahfidz institutions